Searching for a Connection: Prayer and Contemplation "Broadly Conceived" in Thomas Aquinas - Van Nieuwenhove, Rik (Ephemerides theologicae Lovanienses, 2019)
This article considers the connection - or lack of connection - between prayer and contemplation in the writings of St Thomas Aquinas from his Commentary on the Sentences to the Summa Theologiae. The first part examines the meaning of "contemplation" and it demonstrates that Aquinas uses contemplation in a broad and in a more restricted sense. The second part outlines his understanding of prayer, which he primarily conceives of in petitionary terms. Finally, the chapter considers the reasons why Aquinas does not establish a particularly strong connection between contemplation and prayer. Aside from the fact that contemplation is a pursuit of the theoretical intellect while prayer is associated with the practical intellect, there may have been more important considerations (relating to the status of the Dominican vocation and the reception of Aristotle’s philosophy) why Aquinas resists a strongly charismatic and affective notion of contemplation.